2016
DOI: 10.1111/are.13219
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lipid levels affect lipoprotein clearance, fatty acid transport, lipogenesis and lipolysis at the transcriptional level in muscle and adipose tissue of large yellow croaker (Larimichthys crocea)

Abstract: To investigate the effect of dietary lipid levels on lipid metabolism in muscle and adipose tissue of large yellow croaker (Larimichthys crocea), fish (average body weight 150.0 g) were fed to one of three diets with a low (6%), moderate (12%, the control diet) or high (18%) crude lipid level for 10 weeks. The expression of genes related to lipoprotein clearance (lpl, ldlr, lrp1 and srbi), fatty acid transport (cd36, fatp1, fabp3 and fabp11), lipogenesis (fas and dgat2) and lipolysis (atgl, cpt1 and aco) in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Here, in contrast to the liver and intestine, CD36, FATP1‐b, FATP2 and FATP4 expression in the muscle were reduced by increasing dietary lipid. Pervious study indicated that high‐lipid diet could induce a decrease in beta‐oxidation in the muscle of large yellow croaker (Yan et al, ) and rats (Hancock et al, ). Moreover, the beta‐oxidation in salmon is affected by the fatty acid available and probably regulated at the level of fatty acid uptake (Torstensen & Stubhaug, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, in contrast to the liver and intestine, CD36, FATP1‐b, FATP2 and FATP4 expression in the muscle were reduced by increasing dietary lipid. Pervious study indicated that high‐lipid diet could induce a decrease in beta‐oxidation in the muscle of large yellow croaker (Yan et al, ) and rats (Hancock et al, ). Moreover, the beta‐oxidation in salmon is affected by the fatty acid available and probably regulated at the level of fatty acid uptake (Torstensen & Stubhaug, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fish, a protein‐mediated fatty acid uptake has also been characterized in trout (Richars, Bonen, Heigenhauser, & Wood, ), salmon (Zhou, Stubhaug, & Torstensen, ) and grass carp (Zhou et al, ). Furthermore, CD36 and FATP1 have been identified and proposed to facilitate the cellular uptake of fatty acids in several fish species, such as salmon (Sánchez‐Gurmaches et al, ), trout (Sánchez‐Gurmaches, Cruz‐Garcia, Gutiérrez, & Navarro, ), tilapia (He et al, ), large yellow croaker (Yan, Liao, Mai, & Ai, ) and silver pomfret (Liao et al, ). And very recently, FATP4 and FATP6 presence have been assessed in Japanese seabass, and were supposed to be function as fatty acid transporters (Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In present study, HC diet down‐regulated, but HF and HP diets did not affect the muscular lpl mRNA expression. The opposite results were observed in tilapia ( Oreochromis niloticus ) (Tian, Wu, et al, 2015) and large yellow croaker ( Larimichthys crocea ) (Yan, Liao, Mai, & Ai, 2017), and these results suggested that LPL maybe not the marked protein for regulation lipid deposition in muscle.…”
Section: Discussionmentioning
confidence: 92%